Automatic Methods for the Refinement of System Models From the Specification to the Implementation - Seiter, Julia; Wille, Robert; Drechsler, Rolf.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive overview of automatic model refinement, which helps readers close the gap between initial textual specification and its desired implementation. The authors enable readers to follow two "directions" for refinement: Vertical refinement, for adding detail and precision to single description for a given model and Horizontal refinement, which considers several views on one level of abstraction, refining the system specification by dedicated descriptions for structure or behavior. The discussion includes several methods which support designers of electronic systems in this refinement process, including verification methods to check automatically whether a refinement has been conducted as intended.
Introduction -- Preliminaries -- Challenges in Model Refinement -- Verification of Vertical Refinement -- Extraction of a Relation for Vertical Refinement -- Verification of Horizontal Refinement -- Summary and Conclusions.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation